Study of Some Plasma Characteristics in Dielectric Barrier Discharge (DBD) System - Kadhim, Murad M.; Abbas, Qusay A.; Abdulameer, Mohammed R. (Iraqi Journal of Science, 2022)
In this present paper,  an experimental study of some plasma characteristics in dielectric barrier discharge (DBD) system using several variables, such as different frequencies and using two different electrodes metals(aluminium (Al) and copper (Cu)), is represented. The discharge plasma was produced by an AC power supply source of 6 and 7 kHz frequencies for the nitrogen gas spectrum and for two different electrodes metals(Al and Cu). Optical emission spectrometer was used to study plasma properties (such as electron temperature ( ), electron number density ( ), Debye length ( ), and plasma frequency ( )). In addition, images were analysed for the plasma emission intensity at atmospheric air pressure.